Does the cognitive measure Cog‐4 show improvement among patients treated with thrombolysis after acute stroke?. Issue 8 (19th July 2012) - Hajjar, Karim; Fulton, Rachael L.; Diener, Hans‐Christoph; Lees, Kennedy R.; ,; Alexandrov, A; Bath, PMW; Bluhmki, E; Claesson, L; Curram, J; Davis, SM; Donnan, G; et al.
<x xml:space="preserve">Abstract</x> Background Although the established measure of disability post stroke, the modified Rankin Scale emphasizes motor function and may underestimate the importance of cognitive impairment in more disabled patients. A subset of four items from the National Institutes of Health Stroke Scale has been proposed to assess cognitive function after stroke (Cog‐4), and to correlate with modified Rankin Scale. Items correspond to orientation, executive function, language, and inattention. We investigated responsiveness of Cog‐4 to treatment with thrombolysis and whether it offers information that supplements modified Rankin Scale. Methods We included 6268 patients from the Virtual International Stroke Trials Archive: 2734 received intravenous thrombolysis and 3534 were treated conservatively. We compared day 90 outcomes between treated and untreated groups, by modified Rankin Scale (illustrative) and by Cog‐4 (primary measure) adjusting for age, baseline National Institutes of Health stroke scale, hemispheric lateralisation as well as baseline Cog‐4 and baseline National Institutes of Health Stroke Scale excluding baseline Cog‐4 separately. Analysis of Cog‐4 was repeated within strata of 90 day modified Rankin Scale. Statistical analyses included proportional odds logistic regression and Cochran–Mantel–Haenszel test. Results Modified Rankin Scale showed a difference between treatment groups of expected magnitude (odds ratio 1·56; 95% confidence interval 1·43–1·72; P < 0·001). After adjustment for imbalance in baseline prognostic factors, the distribution of Cog‐4 scores at 90 days was better in thrombolysed patients compared with nonthrombolysed patients (odds ratio 1·31; 95% confidence interval 1·18–1·47; P = 0·006). However, Cog‐4 analysis stratified by 90‐day modified Rankin Scale was neutral between treatment groups (OR 1·01; 95% CI 0·90–1·14), and Cog‐4 was not responsive to treatment group even within modified Rankin Scale categories 4 and 5 despite substantial cognitive deficits in these patients. Conclusion Although Cog‐4 may be responsive to treatment effects, it does not provide additional information beyond modified Rankin Scale assessment.